Pendekatan Pembelajaran Culture Responsive Teaching (CRT) Pada Mahasiswa Program Studi Pendidikan Bahasa Jerman - Marantika, Juliaans; Tomasouw, Jolanda (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
Research on the Culture Responsive Teaching (CRT) learning approach aims to ensure that in the learning process the educators or teachers focus not only on improving students' learning achievements, but also on helping students accept and strengthen their cultural identity. This research is semi-qualitative research with the research subjects being students of the German Department with 20 respondents . In this research it is used Integration of CRT aspects in learning among others Content Integration, facilitating Knowledge construction, Prejudice Reduction, Social Justice and Academic Development. As instruments used were questionnaires and interviews. The research results show that students have a high tendency towards the facilitating Knowledge construction aspect with a score of 95%, followed by other aspects, namely Prejudice Reduction (94%), Academic Development (92), Content Integration (89), Social Justice (89). It means that cultural elements are very important in the learning process because they can help students understand reading texts well, because teachers can provide explanations using local culture. So it can be concluded that this CRT approach needs to be applied at various levels of education